Evaluation of periodontal status and treatment needs of the Serbian Armed Forces population - Daković, Dragana; Lekić, Margareta; Bokonjić, Dubravko; Lazić, Zoran; Čutović, Tatjana; Mladenović, Raša (Vojnosanitetski pregled, 2021)
Background/Aim. Periodontal disease is the second most common diseases after dental decay. The aim of the study was to determine frequency and seriousness of the periodontal disease, and periodontal treatment needs among the participants of the Serbian Armed Forces (SAF). Methods. A prospective cross-sectional study carried out on 1,411 military personnel aged 19–64 years (mean age: 35.20 ± 8.46 years). Periodontal health was recorded following the Community Periodontal Index (CPI) of Treatment Needs (CPITN). The frequency distributions were studied with regard to age groups, gender and military rank. The mean number of sextants affected per person was assessed. Results. Only 3% of the total SAF population had healthy periodontal tissue. The highest percentage of the studied population had the presence of calculus (42.7%), and the mean value of sextants with calculus was 1.77 per person. 35.8% of participants had the CPI score 3 (4–5 mm), and 5.4% of participants had the CPI score 4 (≥ 6 mm). Periodontal pockets (CPI score 3 and 4) were mostly present in the upper right (32%) and left (26%) sextant. Almost every subject needed better oral hygiene maintenance, but 41.2% of our participants required complex periodontal treatment. Conclusion. On the basis of all data, the treatment needs of SAF participants are big and vary in relation to the age, gender and military rank. Unfortunately, a dramatically small number of participants in the study had a completely healthy periodontium.